The Level of Public Awareness of the Application of the Electronic Ticket System in Surabaya - Ertien Rining Nawangsari; Koko Prasetya; Muhammad Arifin; Khusnul Khothimah; Rhea Ardhana (Universitas Medan Area, 2020)
In Indonesia, currently there has been progress in the field of information technology. Along with the development of sophisticated and advanced technology, there are more and more demands of need. By utilizing the sophistication and advancement of existing technology, the government makes electronic-based policies, namely e-government. From the existence of this new electronic-based system, it makes easier to carry out the implementation of services carried out by the state apparatus to public. The objective of this study is to measure the level of public awareness of Surabaya people towards the application of the E-ticket system related to frequent violations. The scope of the study is the city of Surabaya. The problem is focused on the level of public awareness about the e-ticket system that has been running. In order to approach this problem, a theoretical reference from Soerjono Sukanto was used regarding public awareness. The data were collected through questionnaires spread across 31 districts in Surabaya and analyzed quantitatively with a descriptive approach. This study concludes that Surabaya people had awareness and knew a new system in ticketing, namely the electronic ticketing system, but for its application, many violations still occured. It is indicated by the percentage of 55% which is included in the fairly high category with a percentage of 70.5% regarding the existence the new system.